ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CSR DAN DAMPAKNYA TERHADAP NILAI PERUSAHAAN - Sulhan, Muhammad (Fakultas Ekonomi, UIN Maliki Malang, 2014)
This research aims to analyze factors that affect the company’s CSR disclosure and to see theimpact of CSR on firm value. The population in this study are all companies listed on the Indonesia StockExchange (IDX) and samples are15 companies manufacturing. Analysis of the data used to test the firsthypothesis is linear multiple regression analysis is to look at the effect of profitability, leverage, institutionalownership, size, and slack resources on the disclosure of CSR, while to test the hypothesis that both areseeing the effect of CSR on firm value, then used a simple linear regression. The results of this study indicatethat the variable profitability, size, and slack resources have a significant impact on CSR. As for the variableleverage and institutional ownership has no significant effect on CSR. The last, variable CSR has a significantinfluenceon the firm value